UNRAVELING THE MAGNIFICENCE OF ENGLISH LITERATURE: A JOURNEY THROUGH. TIME, THEMES, AND CULTURAL IMPACT (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: English literature stands as a towering monument to human creativity and expression, spanning centuries and continents to offer a glimpse into the depths of the human psyche and the complexities of the world around us. From the earliest Anglo-Saxon poems to the postmodern novels of the 21st century, it encapsulates a rich tapestry of themes, styles, and voices that continue to captivate and inspire readers worldwide.